Exploring leadership for learning in an Estonian school context - Reinaru, Daniel; Eisenschmidt, Eve (Frontiers in Education, 2026)
Leaders drawing on a similar repertoire of leadership practices must align their actions to the context. Therefore, this study aimed to explore the Leadership for Learning (LfL) approach in an Estonian school context by examining which associated practices principals implement in their work. The data were drawn from interviews with 13 experienced exemplary school leaders and analyzed thematically in four dimensions: learner-centered goal setting, curriculum development, supporting professional learning, and building a supportive environment. The findings highlight the relevance of LfL in Estonian school context and provide a set of exemplary practices in each of its domains. The study contributes to the existing body of knowledge on global school leadership practice research highlighting the importance of LfL in a specific national setting and providing insights that inform the design of future leadership preparation and support programs in Estonia.